Interrelationship Between Rainfall-runoff of Treated Catchments in Arid Zone of Rajasthan - Murthy, K N K; Gupta, B S; Issac, V C (Annals of Arid Zone, 2016)
This paper aims to explain the statistical verification of the developed techniques to generate maximum surface water yield from treated catchments under prevailing rainfall condition. Various impervious and water proofing surface covers were tested on a catchment model and their efficiency for generating more surface run-off worked out. The Mathematical model developed establishes a dynamic relationship between two major parameters of the hydrologic cycle viz., rainfall and run-off. The model also highlights the relative efficiency of different indigenous materials for harvesting maximum water on an economic basis. Regression equations both linear and quadratic, for each treatment have been worked out.